The effectiveness of asynchronous online role-play on ESL learners’ willingness to communicate - Madzlan, Noor Alhusna; Zulkepli, Noraini; Shukor, Siti Shuhaida; Bahari, Aireen Aina (Journal of Education and e-Learning Research, 2023)
This paper investigates the use of asynchronous online role-play as a learning technique to improve ESL learners’ willingness to communicate. This study proposes two research objectives; to investigate the significant difference in ESL learners’ willingness to communicate before and after performing asynchronous role-play and to identify factors that impact the ESL learners’ willingness to communicate. A mixed-methods approach is used to understand the impact of the intervention. A set of questionnaires, reflective journal entries and a semi-structured interview were administered to tertiary level ESL students. Results from this study revealed that willingness to communicate among the participants in the treatment group significantly increased with the aid of asynchronous online role-play. Other findings identified factors such as self-confidence, teamwork, linguistic and non-linguistic factors as well as technical skills that show the feasibility of the asynchronous online role-play. The practical implications of this study would allow further exploration of learning techniques in the post-pandemic phenomenon of English language teaching and learning.